Treatment Approaches for Atypical CIDP - Menon, Deepak; Katzberg, Hans Dieter; Bril, Vera (Frontiers in Neurology, 2021)
The variants of chronic inflammatory demyelinating polyneuropathy (CIDP) differ not just in their clinical, pathological and electrophysiological characteristics but often in their indifferent response to conventional immunosuppressive agents effective against typical CIDP. High quality evidence is lacking as far as the management of these atypical variants is concerned. In this review, we summarise the treatment approaches to each of these CIDP variants based on existing data. Distal acquired demyelinating symmetric (DADS) has the phenotype of a symmetric, demyelinating sensory, length-dependent polyneuropathy and is frequently associated with paraproteinemia and anti myelin associated glycoprotein (MAG) antibodies. While the management of idiopathic DADS (DADS-I) is same as CIDP, DADS-M response suboptimally and has favourable response to rituximab. Multifocal acquired demyelinating sensory and motor neuropathy (MADSAM) manifests as a chronic progressive demyelinating mononeuropathy multiplex which can evolve to a confluent pattern indistinguishable from CIDP. Evidence favour treating MADSAM with conventional immunomodulatory therapy (IMT) but tends to response less favourably than CIDP. A subgroup of patients present with purely sensory symptoms and are known as pure sensory CIDP or chronic inflammatory sensory polyradiculoneuropathy (CISP), the latter localising to a pre-ganglionic pathology. Both respond well to first line IMT particularly to IVIG but relapse without maintenance. The pure motor CIDP resembles multifocal motor neuropathy with conduction block (MMNCB) and the worsening noted in earlier with steroids was not reproduced in recent studies, but IVIG would remain the first line of choice. Some of the focal forms of CIDP would defy an accurate classification but responds to first line IMT . Similarly most of the patients with focal forms of CIDP respond well to IVIG. In general, atypical CIDP is amenable to treatment with first line IMT but has suboptimal response compared to CIDP. There is evidence for agents such as rituximab especially in DADS-M and can also used in cases refractory to conventional IMTs.